Formalising the informal businesses in the Midlands Province of Zimbabwe: opportunities and challenges - Moyo, Nokuthula G. (International Journal of Multidisciplinary Research Academy, 2016)
This paper sought to investigate the challenges faced by businesses found in the informal sector in their bid to formalize their operations. Through the use of purposive sampling data was collected from informal businesses in Gweru, Zimbabwe and analysed through content analysis. The findings from the research indicate that those in the informal sector face a variety of challenges in their quest to formalize their operations. The challenges include the complexity and cost of the registration procedures, the punitive tax rates which are similar for both established businesses and small business start ups. Recommendations were made for policy makers to curb these challenges so that businesses are formalized.